(untitled) (Global Journal of Management and Business Research, 2023)
This paper assesses the use of Polythene as a packaging product for business organisations in Nigeria. Despite the challenges of polythene usage such as its threat and dangers to the life in the water bodies and marine Eco-systems, the product is still in high demand by supermarkets, grocery stores and homes due to it durability, its easily recyclable, excellent rigidity, extremely lightweight, enhances protection and very economical for packaging in Nigeria. Data were collected via primary data and analysed. Findings revealed that polythene is the most used packaging products by business organisations in Nigeria. The study recommended that recycling and re-usage of polythene products should be encouraged, enforced, invested on and educated on by individuals, organisations and also the government of Nigeria since its demand and usage is more than other packaging products.